Application of Real Options with Binomial Model in the Valuation of the "Oilnergy-2" Oil Field Investment Project - Viasido Sarumpaet (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study analyzes the application of real options valuation using a binomial model in assessing the offshore oilfield investment project OILNERGY-2. The methodology employs the Four-Step Approach developed by Tom Copeland and Vladimir Antikarov to compute the value of embedded options. Traditional capital budgeting techniques, such as Net Present Value (NPV), frequently underestimate project value by neglecting the indirect cash flows arising from managerial flexibility in decision-making. The research identifies two strategic real options within the project: an option to abandon valued at $174,972 and an option to expand valued at $506,432. Utilizing a binomial option pricing model with an annualized volatility of 25%, a risk-free interest rate of 5%, and quarterly time steps, the analysis demonstrates that the incorporation of real options adds value beyond the conventional NPV metric. The aggregated model indicates a total project valuation increase of $174,972 compared to the base-case NPV of $9.5 million. The findings underscore that the real options framework enhances investment decision support by integrating managerial flexibility and uncertainty management. This approach is especially pertinent in oil and gas exploration ventures, which are characterized by high uncertainty and significant sunk costs inherent in upstream investments